Ideologically-Embedded Design: Community, collaboration and artefact. Issue 131 (November 2019) - Détienne, Françoise; Baker, Michael; Bail, Chloé Le
Highlights: Overview of approaches on roles of values in design process. Proposal of the concept of ideology in design. Focus on the community level in design. Explore the roles of ideology and future research directions. Abstract: Values in design have been studied in HCI research as additional design criteria, in the Value Sensitive Design (VSD) approach, and as foundations of the design approach itself, in Participatory Design (PD). In both cases, values are seen as properties of individuals, groups and society. This paper introduces the Ideologically-Embedded Design (IED) approach that situates values on the intermediary level of analysis of communities . IED is illustrated by the analysis of two case studies of communities, the online epistemic community Wikipedia and the socio-technical system of cohousing projects. In each case, the attendant value systems are described, together with the way that they operate with respect to the co-design process and the design artefact, which corresponds to the community designing itself. The role of systems of values in decision-making and artefact design is discussed. In conclusion, approaches to supporting IED are outlined.